2019
DOI: 10.1111/obr.12826
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity among adults in the Gulf States: A systematic literature review of correlates of weight, weight‐related behaviours, and interventions

Abstract: SummaryObesity has increased to an epidemic level in the Gulf States. This systematic review is the first to explore the scientific evidence on correlates and interventions for overweight (body mass index [BMI] ≥ 25) or weight‐related behaviours in the region. A systematic search of peer‐reviewed articles was conducted using PubMed and PsycINFO. Ninety‐one studies were eligible for this review including 84 correlate studies and seven intervention studies. Correlate studies of overweight focused on sociodemogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 92 publications
(452 reference statements)
5
51
1
1
Order By: Relevance
“…Our findings of the greater risk of overweight/obesity in Australian males and for those who are not living alone are consistent with other studies of males living in Tehran and the Gulf States, which showed that overweight and obesity were significantly more prevalent in those who were married [47] or living with a partner and other family members compared with those who lived alone [48]. Socioeconomic status of the household locality did not significantly increase the odds of overweight/obesity for Indigenous people, however the trend appeared to be that people who resided in higher socioeconomic areas were less likely to be overweight/obese than those who lived in the most deprived areas.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings of the greater risk of overweight/obesity in Australian males and for those who are not living alone are consistent with other studies of males living in Tehran and the Gulf States, which showed that overweight and obesity were significantly more prevalent in those who were married [47] or living with a partner and other family members compared with those who lived alone [48]. Socioeconomic status of the household locality did not significantly increase the odds of overweight/obesity for Indigenous people, however the trend appeared to be that people who resided in higher socioeconomic areas were less likely to be overweight/obese than those who lived in the most deprived areas.…”
Section: Discussionsupporting
confidence: 92%
“…The subgroup analysis by pre-pregnancy BMI suggested that the inverse association between total PA and postpartum weight retention retained consistently for women with pre-pregnancy normal weight and underweight, but not for those with overweight and obesity. It could be argued that these women were likely to incur an unhealthy lifestyle and perceived more barriers to change such unhealthy behaviors by themselves unless they participate in targeted interventions [41]. Nevertheless, the finding should be interpreted with care due to a very small proportion of women with pre-pregnancy overweight and obesity engaging a high total PA level (n = 72, 4.5%) in our sample.…”
Section: Discussionmentioning
confidence: 77%
“…The results from this study can serve as a guiding tool for shaping health strategy during this pandemic by health authorities. As Gulf countries grew enormously in wealth, living standards were raised, albeit at a cost of more sedentary and comfortable life routine 5,15,16 . Kuwait had previously developed a 'Kuwait National Programme for Healthy Living (2013-2017)' 17 ; authorities can develop a strategic plan to counter harmful effects of this pandemic on health that are originating from sedentary lifestyle, unhealthy eating patterns and psychological issues.…”
Section: Discussionmentioning
confidence: 99%